A Comparative Discourse Analysis of Gandhian Philosophy and Ayn Rand’s Objectivism: Ethics, Individualism, Social Responsibility, and Architectural Expression in Literary Texts (Architecture Image Studies, 2026)
The present study undertakes a comparative discourse analysis of Mahatma Gandhi’s philosophical writings and Ayn Rand’s Objectivist fiction, examining ethics, individualism, social responsibility, and architectural expression as an ideological and discursive construct. Drawing on Gandhi’s Hind Swaraj and The Story of My Experiments with Truth and Rand’s We the Living, The Fountainhead, and Atlas Shrugged, the study employs qualitative textual analysis informed by Critical Discourse Analysis (CDA). The analysis reveals that Gandhian discourse is marked by moral persuasion, linguistic simplicity, and dialogic engagement, constructing ethics as collective, relational, and socially embedded. In contrast, Rand’s discourse is assertive and absolutist, privileging rational self-interest, individual autonomy, and architecture as a symbolic articulation of creative freedom, ideological resistance, and modernist selfhood. Despite their ideological divergence, both writers mobilize language and architectural symbolism to challenge dominant ethical paradigms and assert alternative value systems. The study demonstrates how philosophical ideologies are linguistically and symbolically sustained through narrative voice, lexical choice, rhetorical structure, and spatial imagination. By integrating discourse analysis with architectural symbolism, the paper contributes to Scopus-indexed interdisciplinary scholarship in literary studies, philosophy, and cultural discourse, foregrounding the interdependence of ideology, form, and ethical practice.